A Behavioral Approach to Water Conservation : Evidence from Costa Rica - Datta, Saugato (World Bank, Washington, DC, 2015)
This paper presents the design a set of three simple and replicable behavioral interventions, which use stickers that can be added to water bills at low cost, and test their impact on water consumption in Belen, Costa Rica, using a randomized control trial. Two of the three interventions were found to decrease water consumption significantly in the months following the intervention. A descriptive social norm intervention using neighborhood comparisons reduces consumption by between 3.7 and 5.6 percent relative to a control group, while a plan-making intervention reduces consumption by between 3.4 and 5.5 percent. While the two interventions have similar results, they are effective on different subpopulations, with the plan-making intervention being most effective for low-consumption households, while the neighborhood comparison intervention is most effective for high-consumption households. The results demonstrate that behavioral interventions, which have hitherto utilized sophisticated software to deliver customized messages, can be effectively implemented by local governments in developing countries, where technology and resource constraints render the sorts of customized messaging that has typically been used to deliver them in developed countries unfeasible. The results further confirm that raising awareness about how much water an individual consumes, and comparing this consumption level with peers, can go a long way in helping change individuals’ behavior regarding the use of a finite resource such as water.